1981
DOI: 10.1126/science.7006082
|View full text |Cite
|
Sign up to set email alerts
|

Lectins of Distinct Specificity in Rhodnius prolixus Interact Selectively with Trypanosoma cruzi

Abstract: Lectins of different activities were found in the crop, midgut, and hemolymph of the insect Rhodnius prolixus. These were not specific for N-acetyl-D-mannosamine, alpha-N-acetyl-D-galactosamine, and alpha- and beta-galactose, respectively. Lectin receptors were detectable in epimastigote but not in trypomastigote forms of Trypanosoma cruzi, a protozoan parasite of the insect and of humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(57 citation statements)
references
References 9 publications
3
54
0
Order By: Relevance
“…It is possible that the interaction of cell-surface glycoproteins with lectins, which have been described in the gut of the insect vector (Pereira et al, 1981), might play a role in the morphogenesis of T. cruzi. Clearly, further biochemical characterization of the glycoconjugates on the surface of T. cruzi will be needed to help clarify their possible role during differentiation of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the interaction of cell-surface glycoproteins with lectins, which have been described in the gut of the insect vector (Pereira et al, 1981), might play a role in the morphogenesis of T. cruzi. Clearly, further biochemical characterization of the glycoconjugates on the surface of T. cruzi will be needed to help clarify their possible role during differentiation of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Blood-sucking arthropods provide a good opportunity to investigate and discuss structural and functional aspects of the lectins and protein-carbohydrate inter actions taking place in the mechanisms of pathogen/ parasite transmission (for review Ingram & Molyneux, 1991). The first milestone paper on tissue specific lec tins of a vector was published on the kissing bug Rhodnius prolixus by Pereira et al (1981). However, most results on vector lectins have come from research on tsetse flies and have shown that tissue specific lectins might play the crucial role in control of tsetse fly infection by African trypanosomes (for review Maudlin & Welburne, 1988;Maudlin, 1991).…”
Section: Lectins In Arthropods and Vector-pathogen Systemsmentioning
confidence: 99%
“…Although many triatomine species are capable of the disease transmission, most of the knowledge on the vectorparasite interactions and the possible role of lectins and lectin-like activities has been derived from few model species, mostly Rhodnius prolixus and Triatoma infestans. In the course of these studies, several hemagglutin activities have been detected in various tissues such as hemolymph, salivary glands, crop and midgut (Pereira et al, 1981 ;Barraco & Loch, 1988;Gomes et al, 1988;Gomes et al, 1991 ;Gregorio & Ratcliffe, 1991 ;Hypsa & Grubhoffer, 1995) and the possible significance of these compounds for T. cruzi deve lopment has been suggested. Since T. cruzi does not invade the host hemocoel and its complete develop ment takes place in gut lumen, the gut agglutinins may be of particular importance in respect of the deve lopment of this parasite.…”
Section: Lectins In Arthropods and Vector-pathogen Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, they are submitted to drastic changes in temperature, pH and osmolarity and are exposed to saliva, gut contents and blood digestion products [12]. Some factors involved in the development of T. cruzi in the gut of the vector have been identified, including a lytic factor [19,20], lectins [21,22] and hemoglobin constituents [23]. Other factors are suggested to trigger T. cruzi metacyclogenesis in vitro, including cAMP, cAMP analogues and adenylyl cyclase activators.…”
Section: Introductionmentioning
confidence: 99%